EXPLORING THE IMPACT OF CONSUMERS’ TRUST IN FOOD AUTHENTICITY ON THEIR PURCHASE INTENTIONS: A CASE OF ‘SEN HUE’ - A LOCAL LOTUS-GRAIN PRODUCT IN CENTRAL VIETNAM - Nguyen, Duc Kien; Dinh Thi Kim, Oanh; Le Thi Thanh, Nga; Truong Tan, Quan; Nguyen H.D., My; Truong Quang, Dung (Economics of Agriculture, 2025)
There has been a significant increase in the global focus on food authenticity, leading people to closely examine the sources and quality of their food. The intricacy of culinary authenticity is shown in a regional lotus-grain product called ‘Sen Hue’, which suggests that they are from Hue, but in reality, they are obtained from other areas. Applying the Heckit model in the two-step approach for a sample of 426 local consumers, the study explored the drivers of the intention to purchase lotus-grain products. Findings from this study indicate that customers who perceive ‘Sen Hue’ lotus-grains as genuine and reliable have a stronger inclination to make a purchase, highlighting the importance of authenticity in the food industry. Stringent regulatory frameworks and labeling regulations are essential for preserving customer confidence. Additionally, this study highlights the need for a multi-pronged approach to understanding consumer behavior in this market by addressing safety, authenticity, and color specificity concerns.